Cobalt nanoparticles as novel nanotherapeutics against Acanthamoeba castellanii - Ayaz Anwar; Arshid Numan; Ruqaiyyah Siddiqui; Mohammad Khalid; Naveed Ahmed Khan (Parasites & Vectors, 2019)
Abstract Background Species of Acanthamoeba are facultative pathogens which can cause sight threatening Acanthamoeba keratitis and a rare but deadly brain infection, granulomatous amoebic encephalitis. Due to conversion of Acanthamoeba trophozoites to resistant cyst stage, most drugs are found to be ineffective at preventing recurrence of infection. This study was designed to test the antiacanthamoebic effects of different cobalt nanoparticles (CoNPs) against trophozoites and cysts, as well as parasite-mediated host cell cytotoxicity. Methods Three different varieties of CoNPs were synthesized by utilizing hydrothermal and ultrasonication methods and were thoroughly characterized by X-ray diffraction and field emission scanning electron microscopy. Amoebicidal, encystation, excystation, and host cell cytopathogenicity assays were conducted to study the antiacanthamoebic effects of CoNPs. Results The results of the antimicrobial evaluation revealed that cobalt phosphate Co3(PO4)2 hexagonal microflakes, and 100 nm large cobalt hydroxide (Co(OH)2) nanoflakes showed potent amoebicidal activity at 100 and 10 µg/ml against Acanthamoeba castellanii as compared to granular cobalt oxide (Co3O4) of size 35–40 nm. Furthermore, encystation and excystation assays also showed consistent inhibition at 100 µg/ml. CoNPs also inhibited amoebae-mediated host cell cytotoxicity as determined by lactate dehydrogenase release without causing significant damage to human cells when treated alone. Conclusions To our knowledge, these findings determined, for the first time, the effects of composition, size and morphology of CoNPs against A. castellanii. Co3(PO4)2 hexagonal microflakes showed the most promising antiamoebic effects as compared to Co(OH)2 nanoflakes and granular Co3O4. The results reported in the present study hold potential for the development of antiamoebic nanomedicine.